PTH-039 The cost-effectiveness of radiofrequency ablation for gastric antral vascular ectasia refractory to first-line endoscopic therapy. (June 2019) - Magee, Cormac; Graham, David; McMaster, Jessica; Leonard, Catherine; Davies, Heather; Banks, Matthew; Sweis, Rami; Lipman, Gideon; Alzoubaidi, Durayd; Hussein, Mohamed; Everson, Martin; Lovat, Laurence; et al.
Abstract : Introduction: Argon plasma coagulation (APC) is the most commonly used treatment within the UK NHS for Gastric Antral Vascular Ectasia (GAVE), a chronic condition that can cause debilitating symptoms secondary to chronic blood loss. This economic evaluation provides a preliminary assessment of the cost-effectiveness of radiofrequency ablation (RFA) in this patient population, which recent evidence suggests may offer improved safety and effectiveness when used to treat APC-refractory GAVE patients. Methods: A Markov model was constructed to undertake a cost-utility analysis for adults diagnosed with GAVE symptomatic of iron-deficiency anaemia. The economic evaluation used a UK NHS and personal social services (PSS) perspective, with a 20-year time horizon, and three-month cycles. Patients transfer between health states defined by haemoglobin level: mild (11 to 12 g dl -1 ), moderate (9 to 10 g dl -1 ) and severe (< 8 g dl -1 ). The clinical effectiveness data were sourced from literature and expert opinion. Resource use and costs were reflective of the UK NHS, and parameter uncertainty was explored using probabilistic sensitivity analysis (PSA). Benefits were qualified using Quality Adjusted Life Years (QALYs), with utility weights taken from the literature. The primary output was the Incremental Cost-Effectiveness Ratio (ICER) expressed as cost per QALY gained. Results: The base case ICER was £13, 933 per QALY gained, with a 58.9% chance that RFA was cost-effective at a threshold of £20, 000 per QALY gained. The model estimated that implementing RFA would result in reductions in the need for intravenous iron, endoscopies and blood transfusions by 27.1%, 32.3% and 36.5% respectively. Compared to APC, RFA was associated with an estimated 36.7% fewer procedures as well as less time in severe health states (1.77 years) and more time in mild health states (1.2 years) when treated with RFA over a 20-year time horizon. Conclusions: These preliminary and novel cost-effectiveness data indicate RFA treatment is likely to be cost-effective for patients with ongoing symptoms of APC-refractory GAVE, and could lead to substantive reductions in health care resource and also have a notable impact on a patient's state of health. As a rare disease, clinical data in this area is limited. Data from ongoing registry studies will support more sophisticated assumptions beyond expert input.